UPAYA PENINGKATAN KOMPETENSI PEDAGOGIK GURU NON KEPENDIDIKAN DALAM PENYUSUNAN PERENCANAAN PEMBELAJARAN MELALUI SUPERVISI AKADEMIK KEPALA SEKOLAH DI SDN 20 TALAWI KECAMATAN KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Desi Maria (STKIP Pesisir Selatan, 2018)
ABSTRACTFrom the Research Process School actions taken at SDN 20 Talawi entitled Improving Pedagogic Competencies of Non Academic Teachers in the Preparation of Learning Implementation Plans through Academic Supervision of the Principal can be concluded that (1) In the Components of Formulating indicators of learning objectives, there is an increase of 40% in ability initial, to 60% in cycle 1 and increased to 70% at the end of the activity (2) In the Component Determination of materials and learning materials, there was an increase in ability from 65% to 70% after cycle 1 and strengthened to 80% (3) In Components The selection of learning strategies and methods, which include learning steps and the determination of the time allocation used, shows a significant increase from the original only 40% to 60% in cycle 1 and increased again to 75% after cycle 2 (4). there is no noticeable increase in the media selection component and learning tools also have an increase of 60% at the beginning of the activity and after cycle 1, to 80% after cycle 2 (5) A significant increase can also be seen in the learning evaluation planning component. From the original only 40% at the beginning of the activity, to 60% at the end of cycle 1 and managed to reach 70% at the end of the cycle 2 (6) Looking at the data obtained from research results in this school action research activity, it can be concluded that academic supervision is carried out by the head schools with 5 teachers who did not have a teacher education background, succeeded in improving their pedagogical competence in developing Learning Planning.Keywords: Pedagogic Competence, Academic Supervision, Learning Planning